ChemInform Abstract: 1, 2‐Bis(ferrocenyl)dipnictenes: Bimetallic Systems with a Pn=Pn Heavy π‐Spacer (Pn: P, Sb, and Bi). Issue 30 (29th July 2014) - Sakagami, Michiyasu; Sasamori, Takahiro; Sakai, Heisuke; Furukawa, Yukio; Tokitoh, Norihiro
Abstract Review: [29 refs.